On Not Being Porn: Intimacy and the Sexually Explicit Art Film - Barker, Anthony (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Since the mid-twentieth century, we have passed from a time where sexual frankness was actively obstructed by censorship and industry self-regulation to an age when pornography is circulated freely and is fairly ubiquitous on the Internet. Attitudes to sexually explicit material have accordingly changed a great deal in this time, but more at the level of the grounds on which it is objected to rather than through a general acceptance of it in the public sphere. Critical objections now tend to be political or aesthetic in nature rather than moralistic. Commercial cinema still seems wary of a frank exploration of sexuality, preferring to address it tangentially in genres such as the erotic thriller. In Europe, an art house canon of sexually explicit movies has formed, starting with Bertolucci’s Last Tango in Paris (1972) and the French-produced In the Realm of the Senses (1976). This article looks at the steps taken since the 1970s to challenge out-of-date taboos and yet at the same time differentiate the serious film about se Xfrom both pornography (operating in parallel with mainstream cinema but in its shadow) and the exploitation film. After reviewing the art film’s relationship with both hard and soft core, two recent films, Intimacy (2000) and 9 Songs (2005), are analyzed for their explicit content and for the way they articulate their ideas about sex through graphic depictions of sexual acts. Compulsive and/or claustrophobic unsimulated sexual behaviour is used as a way of asking probing questions of intimacy (and its filmability). This is shown to be a very different thing from the highly visual and staged satisfactions of pornography.